LITERASI PERBANKAN MAHASISWA (Jurnal Manajemen, 2015)
This research aims to determine the factors that influence the level of banking literacy at university’s students. The factors that are being observed are demographic factors which consist of gender, batch, spending, working/business experience, GPA, and participation in banking education. This research uses random sampling method which was taken from the students of Economics and Business Faculty Universitas Padjadjaran, Bandung. This research uses multiple regression analysis as the methodology. Hypothesis test uses simultaneous test (F-test) and partial test (T-test) with 5% significance level. With Cronbach’s α as much as 0.893 and 206 respondents, the result of this research is  R2 as much as 0,152 and F-test shows that simultanously, independent variable influences dependent variable and the result of t-test shows that partially, gender, batch, working/business experience, and expenses does not affect banking literacy. GPA has a negative coefficient even though during statistical test, it did not give a significant influence. Banking education is the only factor that influence partially. Keywords : Financial Literacy, Banking Literacy, Financial Knowledge